2011
DOI: 10.4028/www.scientific.net/amr.410.228
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Precipitated Calcium Carbonate from Eggshell Powder

Abstract: In this work, PCC was prepared from chicken eggshell powder (ESP) by dissolving 100 g ESP in 1 M hydrochloric acid at room temperature. Under vigorous stirring, PCC was precipitated from the ESP-dissolved solution using 1 M sodium carbonate solution. The dried PESP (precipitated eggshell powder) was then characterized by particle size analyzer, X-ray diffractometer, Brunauer-Emmett-Teller surface analyzer and thermogravimetric analyzer. The particle shape of the PESP was revealed using scanning electron micros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“… 25 The vaterite calcium carbonate is extensively used as a vehicle for encapsulation of drugs or nanoparticles carriers due to its spherical structures. In another study published by our group, 26 discarded eggshell particles were digested in hydrochloric acid, and a mixture of calcite and vaterite particles were obtained after reaction with sodium carbonate. However, no polyelectrolyte was used in those previous studies to stabilise the precipitated particles.…”
Section: Introductionmentioning
confidence: 99%
“… 25 The vaterite calcium carbonate is extensively used as a vehicle for encapsulation of drugs or nanoparticles carriers due to its spherical structures. In another study published by our group, 26 discarded eggshell particles were digested in hydrochloric acid, and a mixture of calcite and vaterite particles were obtained after reaction with sodium carbonate. However, no polyelectrolyte was used in those previous studies to stabilise the precipitated particles.…”
Section: Introductionmentioning
confidence: 99%
“…According to the XRD pattern in figure 5d, crystal polymorphs of the precipitated eCaCO 3 prepared at 35°C was vaterite, whereas that of the ground eggshells was calcite. Sutapun et al also reported that ground eggshells were mainly composed of a calcite crystal structure [43]. The vaterite crystal structure is formed when CaCO 3 is It was deduced that PSS initiated vaterite nucleation through the binding of calcium ions to anionic sulfonate groups, and stabilized the vaterite during crystal growth [29].…”
Section: Characteristic Of Precipitated Eggshell Calcium Carbonate (E...mentioning
confidence: 99%
“…This loss is related to the CO 2 released from CaCO 3 decomposition. Decarbonization of chicken eggshells has been reported to occur in the temperature range of 600-850°C [43,44].…”
Section: Characteristic Of Precipitated Eggshell Calcium Carbonate (E...mentioning
confidence: 99%
“…The XRD analysis was performed on obtained microsphere and diffraction peaks located at 2θ of 20.9 °(004), 24.8 °(110), 27 °(112), 32.8 °(114), 43.7 °(300), 50.1 °(118), and 55.9 °(224) indicated the existence of crystalline phase in vaterite structure. In the related research conducted by Sutapun et al (2012), chicken eggshells were precipitated after digestion in hydrochloric acid with the addition of sodium carbonate in which vaterite and calcite mixture was obtained, and the surface area from untreated chicken eggshell particles increased from 2.55 [m 2 /g] to 4.38 [m 2 /g] after precipitation (Figure 6).…”
Section: Vateritementioning
confidence: 99%
“…SEM microimages of chicken eggshell and precipitated chicken eggshells with a magnification of 3,000 X and 10,000 X, respectively. Reproduced with permission from Trans Tech Publications, Ltd., (Sutapun et al, 2012).…”
Section: Figurementioning
confidence: 99%